2019
DOI: 10.1200/jco.2019.37.15_suppl.6084
|View full text |Cite
|
Sign up to set email alerts
|

A phase II trial cohort of nivolumab plus ipilimumab in patients (Pts) with recurrent/metastatic adenoid cystic carcinoma (R/M ACC).

Abstract: 6084 Background: R/M ACC is a malignant neoplasm most commonly of salivary gland origin with no standard treatment. The impact of combined PD-1/CTLA-4 checkpoint blockade in R/M ACC is unknown. Methods: In a two-stage minimax phase II trial, pts with progressive R/M ACC (non-salivary primaries allowed) were enrolled and treated with nivolumab 3 mg/kg every 2 weeks plus ipilimumab 1 mg/kg every 6 weeks (1 cycle = 6 weeks). Imaging, using RECIST v1.1 response assessment, was scheduled to be performed approximat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(25 citation statements)
references
References 0 publications
1
23
1
Order By: Relevance
“…In the ACC cohort, an ORR of 8.7% was observed (4/46 patients) (53). The combination of ipilimumab and nivolumab was initially thought to improve outcomes; however, only 2 out of 32 patients treated achieved a partial response, with a median PFS of 19.3 weeks in a prospective study (96). As previously stated, ACC appears to lack immune infiltration and harbors a lower mutation burden, being unlikely to benefit from immunotherapy (50).…”
Section: Immunotherapy In Accmentioning
confidence: 99%
“…In the ACC cohort, an ORR of 8.7% was observed (4/46 patients) (53). The combination of ipilimumab and nivolumab was initially thought to improve outcomes; however, only 2 out of 32 patients treated achieved a partial response, with a median PFS of 19.3 weeks in a prospective study (96). As previously stated, ACC appears to lack immune infiltration and harbors a lower mutation burden, being unlikely to benefit from immunotherapy (50).…”
Section: Immunotherapy In Accmentioning
confidence: 99%
“…Four hundred sixty four studies and 452 abstracts were initially retrieved from PubMed search and from 2019 ASCO annual meeting abstracts, respectively. After applying our study selection criteria, 24 clinical trials including 13 trials from PubMed (Wolchok et al, 2013; Antonia et al, 2016b; Hodi et al, 2016; Hammers et al, 2017; Hellmann et al, 2017; Wolchok et al, 2017; D’Angelo et al, 2018; Hellmann et al, 2018; Long et al, 2018; Motzer et al, 2018; Omuro et al, 2018; Overman et al, 2018; Tawbi et al, 2018) and 11 trials from ASCO annual meeting (Bazhenova et al, 2019; Emamekhoo et al, 2019; Fischer et al, 2019; Klein et al, 2019; McGregor et al, 2019; Mielgo et al, 2019; Pelster et al, 2019; Singh et al, 2019; Tchekmedyian et al, 2019; Yau et al, 2019; Zer et al, 2019) were finally included in this meta-analysis. The detailed study selection flow diagram can be seen in Figure 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated that SGCs express PD-L1, PD-L2 and CTLA at varying frequencies of up to 86% [ 12 , 13 , 15 , 16 ]. Also, checkpoint inhibitor therapy leads to dramatic responses in some patients [ 18 , 20 ]. Together with the mentioned results, our findings suggest that inhibition of immune-checkpoint molecules could be an option for systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Another comparable phase II study reported a slightly higher response rate of 16% for SGC (only partial responses) [ 19 ]. Also recently, a phase II trial demonstrated encouraging effectiveness of the PD-1 inhibitor nivolumab in combination with CTLA-4 inhibitor ipilimumab in SGC [ 20 ]. Another study which evaluates the therapeutic use of nivolumab alone is ongoing (NCT03132038).…”
Section: Introductionmentioning
confidence: 99%